Fiscal competition: A bird's eye view - Ricardo Varsano; Sérgio Guimar\~aes Ferreira; José Roberto Afonso (Institute for Applied Economic Research (ipea), 2015)
Fiscal competition is a desirable feature insofar as it promotes a better match between local policies and the preferences of residents, and creates an environment for experimentation of different policies, with the best outcomes surviving through a mechanism of natural selection. Furthermore, fiscal competition may prevent overexpansion of government activities. However, in a world where mobility of economic agents is high and growing, local jurisdictions ability to select and attract firms and individuals through the use of their tax structure and public spending has substantially increased. In such a setting, local governments (as well as states belonging to a federation or sovereign units forming an economic union) may engage in a competition to attract business investment or tax bases, giving rise to all sorts of economic distortions. Moreover, fiscal competition may considerably weaken the redistributive power of government actions. The basic challenge is, therefore, to avoid or reduce the undesirable effects of fiscal competition while preserving all or most of its benefits. Intergovernmental transfers and harmonization of taxation and of other fiscal policies are the most promising instruments to attain this goal.
Keywords: 330